PENGELOLAAN PENERIMAAN NEGARA BUKAN PAJAK: SUATU TINJAUAN EVALUATIF (Studi pada Satuan Kerja Kantor Pertanahan Kabupaten Parigi Moutong) - Angraini, Magfirah; Amir, Andi Mattulada; Yusnita, Nina (Katalogis, 2018)
The study aims are to describe and analyze the management of non-tax revenues; the growth rate and effectiveness of non-tax revenues management; theobstacles faced in the management of non-tax revenues; and the offering alternative solution of non-tax revenues management. The study appliesqualitative method, with the case study approach. Informants are the officials who involve in the management of non-tax revenues atthe Land Office of Parigi Moutong Regency. The results show that non-tax revenues management is not optimal inthephase of planning and budgeting, implementation andadministration, supervision, reporting and accountability as well. The growth rate of non-tax revenues targets (2011-2015) tends to increase, but the realization growth fluctuates annually. The effectiveness (2011-2015) isnot effective due to the realization which does not reach the target. Obstacles faced in the management of non-tax revenues caused by the limited participation of budgeting preparation, lack of human resources both in terms of quality and quantity; weakness of system operational procedures and internal control system, lack of supervision in implementation, and financial report which is still as an administrative formality. Alternative solutions to overcome various obstacles faced, it needs participation in planning and budgeting, employee recruitment, utilization of information technology, increasing supervision on the implementation of system operational procedures, as well as continuous evaluation.